Nonlinear Effects of Performance-Avoidance on Self-Efficacy: A Cusp Catastrophe Model - Stamovlasis, Dimitrios; Stavropoulou, Georgia; Karastergiou, Eleni (Journal of Psychology and Psychotherapy Research, 2021)
Background: achievement goal theory provides an explanatory framework for students’ academic behavior. Reports on performance-avoidance goal orientation have not always been consistent and satisfactorily interpreted. Aims: This study aimed to explore the relation between students’ performance-avoidance goal orientation and self-efficacy by fostering the nonlinear perspective. Methods: In the empirical data cusp catastrophe analysis was applied. Results: The nonlinear model was superior to the linear alternatives and the performance -avoidance goal acted as the bifurcation variable. Conclusions: The behavior of peformce-avoidance is explained as bifurcation factor, signifying a nonlinear system and supporting the complex dynamical system theory (CDS).